Barbershops as venues to assess and intervene in HIV/STI risk among young, heterosexual African American men. - Baker, Jillian Lucas; Brawner, Bridgette; Cederbaum, Julie A; White, Shawn; Davis, Zupenda M; Brawner, William; Jemmott, Loretta Sweet (American journal of men's health, 2012)
African Americans, particularly men, are disproportionately affected by the HIV epidemic. Inconsistent condom use and concurrent sexual partnerships are risk factors; there is limited investigation on how these factors influence HIV risk engagement in young, heterosexual, African American men. To identify contextual risk factors that place young men (18-24 years) at risk for HIV infection, one focus group was conducted with 13 men, and questionnaires were administered to 48 men. Participants were 18 to 24 years old and were recruited from local barbershops. The majority engaged in noncondom use (83%) and had multiple sexual partners (64%). Qualitative themes revealed noncondom use "when in the moment" and enhanced condom use with casual partners. This study provided an understanding of participants' attitudes, intentions, and behaviors as they related to HIV risk and revealed the need for culturally relevant, theory-based HIV prevention programs to reduce HIV transmission among this population.
Keywords: Adolescent; Attitude to Health; Barbering; Focus Groups; Health Behavior; HIV Infections; Humans; Male; Philadelphia; Risk Factors; Sexually Transmitted Diseases; Unsafe Sex; Young Adult